2015
DOI: 10.1111/resp.12701
|View full text |Cite
|
Sign up to set email alerts
|

Absence of airway inflammation in a large proportion of adolescents with asthma

Abstract: Background and objective: Neutrophilic inflammation has been implicated in non-eosinophilic asthma (NEA) in adults, but little is known about NEA in children/adolescents. We assessed clinical and inflammatory characteristics of NEA in adolescent asthma. Methods: Airway inflammation, sputum endotoxin, airway hyper-reactivity, atopy and lung function were assessed in 77 adolescents with asthma and 68 without asthma (12-17 years). Asthma was identified on the basis of wheeze and asthma history. Results: The propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 34 publications
(68 reference statements)
3
30
0
1
Order By: Relevance
“…Atopy was assessed using skin prick tests as previously described 19 using the following aeroallergen solutions: positive control (histamine), negative control (diluent), cat, dog, grass mix, Alternaria , Cladosporium , Penicillium , and house dust mite (Hollister‐Stier Laboratories, Spokane, WA, USA). All tests were read at 15 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Atopy was assessed using skin prick tests as previously described 19 using the following aeroallergen solutions: positive control (histamine), negative control (diluent), cat, dog, grass mix, Alternaria , Cladosporium , Penicillium , and house dust mite (Hollister‐Stier Laboratories, Spokane, WA, USA). All tests were read at 15 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…тканевых структур бронхов, нарушая ме-ханизмы мукозального иммунитета и обусловливая частую заболеваемость острыми бронхитами. Повы-шенный уровень субстанции Р напрямую определял тяжесть и длительность клинической симптомати-ки, патофизиологически вызывая длительный спазм гладких мышц с развитием одышки, отека и гиперсе-креции слизи, обтурирующих дыхательные пути [6].…”
Section: Discussionunclassified
“…Brooks et al . showed that eosinophilic inflammation, defined by >2.5% sputum eosinophils, is absent in 52% of asthma patients, whereas they have comparable increases in symptoms and airflow obstruction . Interestingly, the majority of these non‐eosinophilic asthmatic patients were not found to display any other signs of inflammation such as an increase in neutrophil levels or other inflammatory markers in blood or sputum compared with healthy controls.…”
Section: Asthmamentioning
confidence: 97%